1994
DOI: 10.1093/arclin/9.5.383
|View full text |Cite
|
Sign up to set email alerts
|

How much do 'attention' tests tell us?

Abstract: Twelve measures commonly used to assess attentional processes were examined in a sample of 120 outpatients referred for neuropsychological evaluation. A single factor solution emerged. A second analysis partially replicated factors derived by Shum. McFarland, Bain, and Humphreys (1990). Classification rates (impaired vs. unimpaired) for the measures are presented. The implications of these findings for clinical assessment of attention are discussed

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

1995
1995
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 18 publications
1
11
0
Order By: Relevance
“…The Arithmetic test formed the fourth factor. These findings are in line with previous factor analytic studies of neuropsychological tests (Mirsky et al, 1991;Schmidt et al, 1994).…”
Section: The Five-factor Structuresupporting
confidence: 92%
See 3 more Smart Citations
“…The Arithmetic test formed the fourth factor. These findings are in line with previous factor analytic studies of neuropsychological tests (Mirsky et al, 1991;Schmidt et al, 1994).…”
Section: The Five-factor Structuresupporting
confidence: 92%
“…Mirsky et al (1991) found that many tests loaded onto a "perceptualmotor speed" factor (including Stroop, the Trail Making Test, Digit Symbol Coding, and Digit Cancellation), a "numerical-mnemonic" factor (Digit Span and Arithmetic) a "vigilance" factor (Continuous Performance Test) and a "flexibility" factor (Wisconsin Card Sorting Test). Schmidt et al (1994) found separate factors for "scanning" (Stroop, TMT-A & -B, Digit Symbol Coding) and "spanning" (Visual Span, Digit Span Forwards, Digit Span Backwards).…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Many of the commonly employed attention tests are not based on a theoretical model of attention (Schmidt, Trueblood, & Merwin, 1994;Sohlberg & Mateer, 1989). In addition, factor analyses of these tests have revealed that the set of standard attention tests is multi-dimensional (de Jong & Das-Smaal, 1993;Mirsky, Anthony, Duncan, Ahearn, & Kellam, 1991;Schmidt et al, 1994;Shum, McFarland, & Bain, 1990).…”
Section: Introductionmentioning
confidence: 99%